Risk factors for breast cancer in women who use a basic health unit: descriptive study - Silva, Anna Paula Souza da; Pinto, Francisco José Maia; Sousa, Francisco Stélio de; Mourão, Carla Monique Lopes; Lopes, Marcos Venícios de Oliveira; Fernandes, Ana Fátima Carvalho (Online Brazilian Journal of Nursing, 2011)
Aimed to evaluate risk factors for breast cancer in women who used a Basic Health Unit in Fortaleza. Quantitative study, carried out from March to November 2009 with 320 women. It was used for a data collection form. Among the participants, 206 (64.38%) reported menarche over twelve years, 238 (74.38%) had their first pregnancy below 30 years, 210 (65.63%) breastfed their children, it was found that 177 (55.31%) reported using oral contraceptives, 71 (22.19%) had a family history of breast cancer, 62 (19.38%) were smokers, 89 (27.81%) consumed alcohol. It is noteworthy that even with the technology developed for the control of breast cancer, one can’t ignore the many factors that make up its etiology. Hence, the need for nurses show greater effectiveness in the early recognition of risk factors.